Identifying pattern in global developmental delay children: A retrospective study at King Fahad specialist hospital, Dammam (Saudi Arabia) - Hafiz Habibullah; Raidah Albradie; Shahid Bashir (MDPI AG, 2019)
Global developmental delay (GDD) and intellectual disability are relatively common in pediatric neurology conditions. A retrospective study was designed to analyze risk factors and clinical features in children with GDD at our hospital. No previous data is available on GDD from Saudi Arabia. This study was conducted at king Fahad specialist hospital Dammam (KFSHD) of 134 GDD children (82, 61% males, 52, 39% females), (age 1-9 years). They were assessed by using Griffith Mental Development Scales for (0-2) years and 3-8 years old in locomotors, personal/social, communication, eye & hand co-ordination, performance and practical reasoning. Patients with ASD and non-cooperative behavior were excluded. 75% had developmental delay since birth while 84% had no problem during pregnancy. 22% had birth weight below 2.5 kg. 56% had epilepsy and 57 % had interfamily marriages. 51% were diagnosed cases in the present study. 40% had genetic cause, 25% had metabolic problem, 58% had neuroradiology abnormality and 45% had EEG abnormalities. There a variety of delays in development (speech and language variant, global delay, and the motor variant) noted and are commonly seen in a clinical practice in KFSHD. Longitudinal research beginning in early development will help to understand the developmental domains and neurological comorbidities in these children at high risk for neurodevelopmental disorders.